Improving the Economy of Fish and Shrimp Cultivation Through the Implementation of E-Business - Pranata, Adityya Eka; Kamisutara, Made; Muchayan, Achmad (NAROTAMA UNIVERSITY, 2024)
Based on data from the Lamongan Regency Fisheries Service released in 2020, the total production of fish and shrimp cultivation reached 59,728.16 tons in 27 fisheries development areas throughout Lamongan Regency. And for the village of Bogobabadan capable of producing 2 tons per year. However, currently the marketing of fish and shrimp cultivation business products in the city of Lamongan is still not optimal and only uses traditional techniques, which are only distributed to industrial factories and conventional business sectors around the development area and sold to collectors at prices below market prices. The objectives of this research are (1) to implement E-business for fish and shrimp farming in Lamongan. (2) what are the benefits obtained after implementing e-business for fish & shrimp farming. The subjects of this study were fish and shrimp cultivators in the village of Bogobabadan, Karang Binangun District, Lamongan Regency. The method used is using SWOT analysis (Strength, Weakness, Opportunities, Threats) and as an E-Business solution design using Usecase Diagrams, Activity Diagrams and User Interface / UI Website Design. The results obtained from this study can help fish and shrimp farmers to increase product sales through an online system.